Aid project proliferation and absorptive capacity - David Roodman (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Much public discussion about foreign aid has focused on whether and how to increase its quantity. But recently aid quality has come to the fore, by which is meant the efficiency of the aid delivery process. This paper focuses on one process problem, the proliferation of aid projects and the associated administrative burden for recipients. It models aid delivery as a set of production activities (projects) with two inputs—the donor's aid and a recipient-side resource—and two outputs—development and `throughput', which represents the private benefits of implementing projects, from kickbacks to career rewards for disbursing. The donor's allocation of aid across projects is taken as exogenous while the recipient's allocation of its resource is modelled and subject to a budget constraint. Unless the recipient cares purely about development, an aid increase can reduce development in some circumstances. Sunk costs, representing for the recipient the administrative burden of donor meetings and reports, are introduced. Using data on the distribution of projects by size and country, simulations of aid increases are run in order to examine how the project distribution evolves, how the recipient's resource allocation responds, and how this affects development if the recipient is not a pure development optimizer. A threshold is revealed beyond which marginal aid effectiveness drops sharply. It occurs when development maximization calls for the recipient to withdraw from some donor-backed projects, but the recipient does not, for the sake of throughput. Donors can push back this threshold by moving to larger projects if there are scale economies in aid projects.
Keywords: F35; O12; O19; O20; 330; foreign aid; absorptive capacity; project proliferation; Entwicklungshilfe; Entwicklungsprojekt; Projektbewertung; Theorie